Sleep phenotyping in a rat model of susceptibility to substance use disorders - Eleonora Ficiarà; Oluwatomisin O. Faniyan; Reyila Simayi; Federico Del Gallo; Marisa Roberto; Roberto Ciccocioppo; Michele Bellesi; Luisa de Vivo (PLoS ONE, 2025)
Alcohol use disorders (AUD) are bidirectionally associated with significant sleep disturbances, yet the underlying neural mechanisms remain poorly understood. The Marchigian Sardinian alcohol Preferring (msP) rat is a validated preclinical model that mirrors several genetic and behavioral traits of patients with AUD. This study aimed to characterize the sleep-wake architecture and EEG spectral activity in naïve msP rats compared to Wistar controls. We performed 24-hour polysomnography recordings, revealing that male msP rats (n = 9) spent 7.5% more time awake and less time in NREM sleep relative to Wistar rats (n = 9). This was accompanied by a more fragmented sleep-wake pattern, with a higher number of waking and sleep episodes, state transitions, and sleep fragmentation index. Spectral analysis demonstrated lower high-frequency power, with significant reductions in sigma and beta power during NREM sleep and increased theta/beta ratios during wakefulness. Slow-wave activity, an indicator of sleep pressure, showed a blunted rise and fall across the sleep cycle in msP rats, with reduced amplitude and slope of slow waves during early sleep. Moreover, msP rats exhibited decreased spindle activity, with significantly lower spindle incidence, amplitude, and duration. These findings suggest that msP rats display significant sleep disturbances, including disrupted NREM sleep and altered spectral characteristics in brain activity that partially resemble changes reported in individuals with AUD. This altered sleep profile may reflect neural circuit dysfunctions linked to substance use vulnerability, offering potential insights into the neurobiological basis of sleep disturbances in these complex neuropsychiatric disorders.